The role of physical education in shaping soft skills and self-regulation in senior students: an economic perspective - Artem Synytsia; Ihor Koval; Serhii Kuzhelnyi; Serhii Dzhemesiuk; Serhii Kudin; Andrii Kuzhelnyi; Tatiana Zhlobo; Lidiia Zhula (Sport TK)
This study aimed to analyse the impact of physical training on the formation of soft skills and self-regulation in high school students. It examined key competencies such as leadership, communication, emotional intelligence, and self-regulation, using literature analysis, theoretical synthesis, and a review of physical education practices to identify effective methods for skill formation. The study results confirm that various types of physical activity, such as sports, yoga and cycling, contribute to developing leadership, communication and cooperation skills. It highlights how integrating physical exercises and sports into the curriculum fosters independence, stress resilience, and academic success. Analysis of international Eurobarometer data demonstrated a close connection between students' physical activity and their psychological state, improved academic achievement and ability to manage stress. Integrating balanced programmes into the school system can effectively improve the quality of education and develop well-rounded students ready to meet the challenges of modern society. The findings emphasize the need for investments in education that support holistic student development, blending physical, emotional, and social growth. In conclusion, systematic physical education significantly enhances both personal qualities and academic outcomes, with future research needed to design and test innovative programmes focused on students' comprehensive well-being and success.